2003
DOI: 10.1016/s0735-1097(02)02934-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of acutely ischemic myocardium using ultrasonic strain measurements

Abstract: In this model of acute ischemia, ultrasonic strain indexes differentiate acutely ischemic segments from both normal and dysfunctional myocardium. This should be a promising new approach to the bedside monitoring of acute ischemic changes in regional myocardial function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
11

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(106 citation statements)
references
References 31 publications
4
91
0
11
Order By: Relevance
“…Several studies showed that a significant delay occurred in the timing of maximal segmental thickening during acute ischemia, that is, post-systolic shortening [24]. Therefore, in such condition, postsystolic strain is larger in magnitude than end-systolic strain.…”
Section: Assessment By Strain Measurementmentioning
confidence: 99%
“…Several studies showed that a significant delay occurred in the timing of maximal segmental thickening during acute ischemia, that is, post-systolic shortening [24]. Therefore, in such condition, postsystolic strain is larger in magnitude than end-systolic strain.…”
Section: Assessment By Strain Measurementmentioning
confidence: 99%
“…Therefore, parameters of diastolic function can provide incremental information in identifying the extent of myocardial necrosis compared with indexes of systolic function in patients with coronary artery disease. In this regard, it is possible to assess regional function objectively using strain Doppler imaging (9,13,19). We therefore underwent this experimental study in dogs to test the hypothesis that compared with systolic function measurements, the assessment of diastolic function by strain Doppler echocardiography will provide the more accurate estimate of the extent of viable myocardium.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] It is frequently observed in patients with CAD presenting with LV asynergy. [23][24][25] Earlier studies have demonstrated the presence of abnormal diastolic function in patients with CAD without evidence of systolic wall motion abnormalities by radionuclide angiography or digitized cineangiography.…”
Section: Discussionmentioning
confidence: 99%
“…Both clinical [3][4][5] and animal studies [6][7][8][9][10] have demonstrated that PSS is related to myocardial ischemia.…”
Section: Editorial P 37mentioning
confidence: 99%